Pot experimental of H2S spent AC adsorbent as a potential green soil conditioner to enhance plant growth / Nur Alis Zainuddin - Zainuddin, Nur Alis (2022)
AC is a carbon-rich stable substance with highly porous material that has been used for H2S removal from gas streams. However, the spent AC generated from the H2S removal may lead to the waste management issue since it is listed as schedule waste in Forth Schedule of the Environmental Quality Regulations 2005. Due to its physical and chemical characteristics, spent AC may be potentially utilized as a soil conditioner. The main objective of this study was to investigate the effect of H2S spent Activated Carbon (AC) adsorbents on the plant growth via pot experimental and to analyse the characteristics of used soil and H2S spent AC adsorbents as a potential green soil conditioner. Initially, raw AC and spent pre-oxidized AC were subjected to H2S adsorption process. Then, three (3) different spent adsorbents: (1) raw AC, (2) H2S spent AC and (3) H2S spent pre-oxidized AC were tested on chili’s plants for about 2 weeks. Finally, the analysis of plant growth was done by using Statistical Package for the Social Sciences (SPSS). Besides, the characterization of H2S spent adsorbent and used soil were attempted by using Bruner-Emmett-Teller (BET) and Inductively Coupled Plasma - Optical Emission Spectrometry (ICP-OES). As a result, the H2S spent pre-oxidized AC yielded the highest plant growth compared to H2S spent AC and raw AC. Besides, the H2S spent pre-oxidized AC showed a large surface area and micropore volume (553.2027 m2/g and 0.331428 cm3/g) compared to raw AC (518.4858 m2/g and 0.303345 cm3/g). Lastly, all treated soil comprised of Mg, Ca, Cd, Zn, Mo, Co, Cu, Mn, Fe and Ni, with Fe had the highest concentration in H2S spent pre-oxidized AC (122.8 mg/L). In a nutshell, H2S spent pre-oxidized AC is the best soil conditioner to boost chili’s plant compared to the H2S spent AC and raw AC due to high surface area, large micropore volume and consisted of various minerals and heavy metal contents.